Start-ups – ready to provide vocational education and training? : Seeking areas of potential for greater participation in training - Wagner, Pia [Verfasser]; Samray, David [Verfasser]; Bör, Nicolai [Verfasser] (My University, 2022)
"Despite a high demand for skilled workers and personnel recruitment difficulties, start-ups have been very unlikely to provide vocational education and training (VET) thus far. This article investigates the causes of this absence from training and discusses possible approaches towards increasing participation in training by start-ups. Its examination is based on results from an online survey of start-ups conducted between February and July 2021 and on qualitative interviews carried out to supplement this survey." (authors' abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; 370; Betrieb; Unternehmensgründung; Ausbildungsverhalten; Ausbildungsbetrieb